Gestión de talento humano en el Gobierno Autónomo Descentralizado del Cantón San Francisco de Puebloviejo en el período 2023. - Moran Romero, Joisy Jadely (2024)
In this study, the problem of human talent management in the GAD of Puebloviejo was addressed during the period 2023, with the main objective of understanding what the situation was like in the entity to consequently establish suggestions that allow improving the effectiveness and efficiency of its functions. To carry out this research, interviews were applied to a sample of employees and a survey was conducted to the Director of the Human Talent Department of the government entity where problems of job dissatisfaction and difficulty in attracting qualified personnel were identified. Consequently, strategies were proposed to improve the performance and effectiveness of the functions of the institution.